High Physiological 18F-FDG Uptake in Normal Pituitary Gland on Digital PET Scanner - Jain, Anjali; Usmani, Sharjeel; Al Riyami, Khulood; Mittal, Avni; Abubakar, Sofiullah; Al Busaidi, Asiya; Kheruka, Subhash Chand; Al Sukaiti, Rashid (World Journal of Nuclear Medicine, 2024)
Purpose Recently developed digital positron emission tomography/computed tomography (PET/CT) scanners (digital PET [dPET]) have given new dimensions to molecular imaging. dPET scanner has very high sensitivity, spatial resolution, and image contrast that leads to increased uptake of signal in small-volume structures like pituitary gland (PG) making them visible on PET/CT scan even in absence of any pathology. Adequate knowledge of physiological fluoro-2 deoxy D glucose uptake in PG is required in interpretation of dPET for correct diagnosis and reducing unnecessary additional imaging. The aim of this study is to evaluate the frequency of physiological PG uptake on dPET.Material and Methods Eighty-eight subjects (mean age, 54.44 ± 14.18 years; range, 26–84 years; 63 females and 25 males) with normal PG on magnetic resonance imaging brain and imaged within 6 months on dPET were included in this research study. Out of 88 patients, 20 control subjects (mean age, 58.15 ± 11.08 years: 15 females and 5 males) underwent PET/CT on conventional PET. All images were acquired with similar and standard acquisition protocol and reconstruction done with Time of flight with Point spread function. PG uptake was compared visually and quantitatively.Results PG uptake was seen in 43 patients (48.8%). Out of 43 patients, 31 (72%) showed low uptake, 11 (26%) showed intermediate grade of uptake, and 1 patient (2%) showed intermediate-to-high uptake and was categorized as high-grade uptake. In the control group of 20 patients, 3 (15%) showed low uptake, while none of them showed intermediate or high uptake.Conclusion Physiological PG uptake is commonly seen on dPET. Low-to-intermediate grade of PG uptake on dPET in an asymptomatic patient is physiological and does not require further evaluation and should be reported with caution.
Keywords: 18F-FDG PET/CT; pituitary gland; digital PET; conventional PET